Graphene science handbook. Nanostructure and atomic arrangement - Aliofkhazraei, Mahmood; Ali, Nasar; Milne, W. I. (William I.); Ozkan, Cengiz S.; Mitura, Stanislaw, 1951-; Gervasoni, Juana L. (Boca Raton : CRC Press, 2016)
Graphene is the strongest material ever studied and can be an efficient substitute for silicon. There is no other major reference work of this scope on the topic of graphene, which is one of the most researched materials of the twenty-first century. The set includes contributions from top researchers in the field and a foreword written by two Nobel laureates in physics. This volume in the set focuses on nanostructure and atomic arrangement--
section 1. Atomic arrangement and defects -- section 2. Modified graphene -- section 3. Characterization -- section 4. Recent advances.
Keywords: Graphene -- Handbooks, manuals, etc; Nanostructured materials -- Handbooks, manuals, etc